Phase separation and crystal precipitation in supercooled sulphophosphate ionic melts - Reibstein, S.; Da, N.; Simon, J. -P.; Spiecker, Erdmann; Wondraczek, Lothar (Physics and Chemistry of Glasses-European Journal of Glass Science and Technology Part B, 2012)
Sulphophosphate melts of the type SO3-P2O5-EO-A(2)O (E=Zn2+, Ca2+, Sr2+, Ba2+, Mg2+, Mn2+; A=Li+, Na+, K+) enable fabrication of surprisingly stable ionic glasses. Depending on the P/S ratio, their structure may be characterized by chemical heterogeneity on short length scales, where different cations cluster in the vicinity of different anions. To evaluate the topological origin and the kinetics of phase separation and crystallisation, in situ small angle x-ray scattering, transmission electron microscopy, laboratory x-ray diffraction and calorimetric analyses were employed. Volume crystallisation occurs in a two-step process of microscopic phase separation and diffusion-controlled two-dimensional growth of sulphate phases. The crystallisation mechanism depends largely on SO3 content and appears to be directly related to the topological heterogeneity of the precursor melt.